Anglicising the Egyptian song: Arabic-English switching in Egyptian Arabic - Abdelreheem, Hasnaa (Universitas Jambi, Magister Program of English Education Department, 2023)
In light of the presence of English in the Egyptian everyday life activities on various syntactic levels, this study is an attempt to approach borrowing and code-switching in Egyptian music from the dominance of linguistic system perspective. The study aimed to determine whether the Arabicâ€“English switching instances in Egyptian music are borrowed forms or code-switches. In addition, it is an attempt to investigate the syntactic categories and types of switches to English as well as the contextual and functional reasons behind the switches through the observation of the relationship between the switches and the theme/situation/context where they appeared in the corpus. The data selected for the quantitative and qualitative analyses constituted a sample of five Egyptian songs that tackle youth-related themes and issues, not addressed in the mainstream music. The instances of borrowing the corpus provided indicated that the phonological and morphological adaptation to Egyptian Colloquial Arabic patterns occur across a continuum (from full integration to no integration) in the form of three strategies: â€œdirect insertionsâ€, â€œindirect insertionsâ€ and â€œlight borrowingâ€. Two types of code-switching (â€œinter-sentential code-switchingâ€ and â€œintra-sentential code-switchingâ€) were employed in two songs out of the five selected. The analyses indicated that English continues to serve as a source language for technology, social media and fashion-related diction that have found their way towards playing a vital role in everyday life communication among young Egyptians, including monolinguals and less proficient bilinguals.